AI as a New Conversational Partner in the Era of Burnout: Psychological Mechanisms, Risks, and Opportunities for Medicine - Rusanov Володимир (Psychosomatic Medicine and General Practice, 2025)
Background. In the digital age, the traditional phenomenon of doomscrolling (the compulsive consumption of negative news content) is gradually transforming into a new practice — AI-companionship, intensive interaction between users and generative language models in the form of dialogue. Unlike passive information consumption, interaction with AI takes on the character of cognitive and social partnership, opening new opportunities for self-reflection, learning, and psychosocial support. This trend is particularly significant in medicine, where high levels of emotional burnout among physicians and healthcare professionals create an urgent demand for innovative tools of psychological assistance. At the same time, risks remain: dependency on digital companions, the illusion of “algorithmic truth,” and the gradual replacement of live human interaction. Objective. The aim of this study is to theoretically define and analyze the phenomenon of AI-companionship, to identify its psychological mechanisms, potential risks, and positive possibilities in the context of cognitive and social practices, as well as its potential role in the prevention of emotional burnout among healthcare professionals. Materials and Methods. The article applies an interdisciplinary approach, including a theoretical review of literature in cognitive psychology, sociology of technology, and digital communication; conceptual frameworks of algorithmic authority, cognitive outsourcing, and digital companionship; and a comparative analysis of empirical studies on chatbot applications in mental health, educational practices, and professional burnout prevention (EU/USA, 2015–2023). Results. It was found that trust in AI is based on three mechanisms: the perception of algorithms as objective and neutral (algorithmic authority); the delegation of cognitive functions to machines (cognitive outsourcing); and the formation of quasi-social bonds (digital companionship). The study demonstrates that AI can serve as a tool for self-reflection, psychoeducation, and primary support (an analogue of a “digital psychotherapist”), as well as functioning as a consultant (“family office”) in matters of career, integration, and life strategies. For healthcare professionals, AI can provide cognitive offloading (fast access to protocols and clinical guidelines), act as an additional emotional buffer, and deliver micro-interventions in everyday practice that may help reduce burnout risks. At the same time, the study identifies risks such as overreliance on algorithmic outputs, erosion of real social interactions, and new forms of digital dependency. Conclusions. The phenomenon of AI-companionship can be understood as a new form of “algorithmic mirror,” reflecting and amplifying users’ cognitive and social processes. In the case of healthcare professionals, it may serve as an auxiliary resource for the prevention of emotional burnout, but only as part of a comprehensive, multi-level strategy that includes organizational reforms and psychotherapeutic interventions. The optimal model is a hybrid one, in which AI complements but does not replace human experts and established support systems. Future research should focus on the empirical evaluation of large language models’ effectiveness in reducing burnout among healthcare professionals and their integration into healthcare systems. Key words: artificial intelligence, emotional burnout, medical stuff, mental health care, carepsychoeducation, professional burnout